The Potential of Microextraction Techniques for the Analysis of Bioactive Compounds in Food - Pereira, Jorge A. M.; Casado, Natalia; Porto-Figueira, Priscilla; Câmara, José S. (Frontiers in Nutrition, 2022)
For a long time, the importance of sample preparation and extraction in the analytical performance of the most diverse methodologies have been neglected. Cumbersome techniques, involving high sample and solvent volumes have been gradually miniaturized from solid-phase and liquid-liquid extractions formats and microextractions approaches are becoming the standard in different fields of research. This includes the analysis of bioactive compounds in foods that will be the focus of this review. But microextraction also represents an opportunity to mitigate the environmental impact of organic solvents usage, as well as lab equipment. For this reason, in the recent literature, phenolics and alkaloids extraction from fruits, medicinal herbs, juices, and coffee using different miniaturized formats of solid-phase extraction and liquid-liquid microextraction are the most popular applications. However, more ambitious analytical limits are continuously being reported and emergent sorbents based on carbon nanotubes (CNTs) and magnetic nanoparticles (MNPs) will certainly contribute to this trend. Additionally, ionic liquids (ILs) and deep eutectic solvents (DES) constitute already the most recent forefront of innovation, substituting organic solvents and further improving the current microextraction approaches.